Time as a subject-matter of philosophical reflection in the context of activity approach - Soloshсhenko, P.P.; Karakonissova, S.G. (Ye.A.Buketov Karaganda State University Publ., 2015)
The article deals with the problem of interrelation of time with activity and consciousness of the person. The authors conduct a social and philosophical analysis of the main stages of establishment of philosophical category of time. The results of this analysis allow assuming the idea about conscious coordination of different time rhythms — space, biospheric, social and personal — and to determine perspectives to form new culture of time mastering in society.
Əрекеттік көзқарас тұрғысынан уақыт философиялық рефлексияның пəні ретінде
Время как предмет философской рефлексии в контексте деятельностного подхода
Keywords: human; time; time rhythms; activity; social activity; philosophical reflection; social and philosophical analysis